2019
DOI: 10.1371/journal.pone.0211688
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough tuberculosis disease among people with HIV – Should we be worried? A retrospective longitudinal study

Abstract: IntroductionIsoniazid preventive therapy (IPT) is a proven means to prevent tuberculosis (TB) disease among people living with HIV (PLHIV). However, there is a concern that patients often develop tuberculosis disease while receiving IPT, defined here as breakthrough tuberculosis, which may affect treatment outcome. In this study, we assessed the magnitude and determinants of breakthrough tuberculosis.MethodsA multisite retrospective longitudinal study from the year 2005 to 2014 involving 11 randomly selected h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…PLHIV who were on HAART had 87% reduced risk of EPTB compared to those who were not enrolled on HAART (AHR = 0.134, 95%CI = 0.075-0.238). In line with this, other studies also reported the significant decrease risk of EPTB among HIV positive individuals who were enrolled on HAART [6,22,30,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…PLHIV who were on HAART had 87% reduced risk of EPTB compared to those who were not enrolled on HAART (AHR = 0.134, 95%CI = 0.075-0.238). In line with this, other studies also reported the significant decrease risk of EPTB among HIV positive individuals who were enrolled on HAART [6,22,30,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 73%
“…Immune status is a key factor for the susceptibility of a host for TB, such that when the immune system becomes week the likely hood to be infected with TB increases [6] [24]. Based on this study and findings from previous studies done in Ethiopia and other countries, individuals who had lower CD4 count at the time of enrollment had higher risk to develop TB [2,6,14,20,21,23,[26][27][28][29][30][31][32][33]. The other independent predictor of EPTB observed in this study was the baseline hemoglobin value.…”
Section: Discussionmentioning
confidence: 84%
“…Nonetheless, limitations related to our study include that our findings cannot be generalized to the entire population as the data is generated from the private sector and included only one study site. The diagnosis of TB in SSA setting is challenging as it is not definitive being without microbiological confirmation for all patients [14,15,21,47,49,50], as is for our cohort. All our patients received IPT for preventing TB as of 2010.…”
Section: Discussionmentioning
confidence: 97%
“…The dataset used in this study is publicly available through the PLOS ONE policy, and comprehensive details on the selection of study participants that provided data analysed in this study are described elsewhere [ 5 ]. The following is a brief description of the study design, population, setting, exposure variables and outcomes, data collection procedures and ethical consideration.…”
Section: Methodsmentioning
confidence: 99%
“…These methods assume non-informative censoring and failures from competing risks are treated as censored [ 2 ]. However, in the competing risks paradigm, the occurrence of competing events can result in informative censoring [ [2] , [3] , [4] , [5] , [6] ]. Failure to account for competing events may reduce statistical power, overestimate probability of outcomes of interest and result in biased inferences [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%